KOMPOSISI N-PROTEIN DAN ASAM AMINO PRODUK FERMENTASI TRADISIONAL INA SUA DARI MALUKU TENGAH - Nara, Selfia; Ijong, Frans G.; Suwetja, I Ketut; Onibala, Hens (Pascasarjana Unsrat, 2013)
Ina sua is a traditional salted fish originated from Centre Molluca (Teon, Nila, Serua) in which is processed by fermentation during a certain time. The research on the compotition of nutrion as well as amino acid of this product is still rare done. There for the current research is to analyze the compotition of N-protein and amino acid of ina sua during fermentation process. The results show that ina sua has 16 types of amino acids consisting of 9 amino acids esential and the rest were 7 amino acids non esential. The highest content of amino acids were glutamate acids (3,384%) and the lowest one was histidin (0,527%), while the content of N-protein were ecresed during fermentation process up to 12 weeks.